2007
DOI: 10.1007/s10637-007-9060-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro chemosensitivity of freshly explanted tumor cells to pemetrexed is correlated with target gene expression

Abstract: These results form a rational basis for the design of clinical trials to evaluate the expression of these enzymes as predictors for treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 20 publications
1
58
0
1
Order By: Relevance
“…Sensitivity to pemetrexed was also associated with mRNA levels of genes involved in the mechanism of action of this drug in freshly explanted human tumor specimens. In particular, low TS mRNA, as well as reduced levels of GARFT and DHFR mRNA, significantly correlated with chemosensitivity to pemetrexed [34]. Several other studies showed that the expression of TS protein was correlated with outcome in NSCLC specimens from patients treated with pemetrexed-based chemotherapy, particularly in nonsquamous carcinomas [35,36].…”
Section: Pharmacogenetics Of Pemetrexedmentioning
confidence: 89%
“…Sensitivity to pemetrexed was also associated with mRNA levels of genes involved in the mechanism of action of this drug in freshly explanted human tumor specimens. In particular, low TS mRNA, as well as reduced levels of GARFT and DHFR mRNA, significantly correlated with chemosensitivity to pemetrexed [34]. Several other studies showed that the expression of TS protein was correlated with outcome in NSCLC specimens from patients treated with pemetrexed-based chemotherapy, particularly in nonsquamous carcinomas [35,36].…”
Section: Pharmacogenetics Of Pemetrexedmentioning
confidence: 89%
“…To evaluate the possible role of breast cancer resistance protein (BCRP) and multidrug-related proteins (MRPs) expression on pemetrexed sensitivity, as suggested in a study on freshly explanted human tumor specimens (Hanauske et al, 2007), we performed Western blot analysis of BCRP, MRP1, MRP2, MRP3, MRP4, and MRP5 expression in the panel of NSCLC cells. Total lysates were prepared in buffer containing 50 mM Tris, pH 7.6, 20% (v/v) glycerol, 5 mM dithiothreitol, 0.5% (v/v) Nonidet P-40, and 4.0% (v/v) of a protease inhibitor cocktail.…”
Section: Erlotinib and Pemetrexed In Nsclc 1291mentioning
confidence: 99%
“…Therefore, most studies have focused on pemetrexed effects on TS. TS mRNA levels were inversely correlated with pemetrexed activity in different tumor cells (19,20), whereas other studies suggested a correlation between high levels of TS protein expression and reduced sensitivity to pemetrexed in colon and lung cancer cells (21,22). Furthermore, TS mRNA and protein expression were predictive of responsiveness in patients with advanced breast cancer treated with pemetrexed alone and in NSCLC patients treated with pemetrexed/gemcitabine neoadjuvant therapy, respectively (23).…”
Section: Introductionmentioning
confidence: 98%